Political Education of Political Parties in Sumbawa District Ahead of The 2024 Legislative Elections - Irwansyah, Irwansyah; Kariyani, Leni Nurul; Hidayat, Rahmat (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research provides an in-depth analysis of